Be opened! : the Catholic Church and deaf culture - Portolano, Marlana (The Catholic University of America Press, 2021)
"In this history of deafness and sign language in the Catholic Church, the author draws on the stories of deaf priests and pastoral workers to trace the development of an active language minority in today's global church"--